DEVELOPMENT OF TEV SENSOR FOR HVDC CABLE - Khoirul Huda, Muhammad
The occurrence of partial discharges (PD) is a crucial criterion for evaluating insulation quality and for DC voltage applications. However, interpreting PD is significantly more challenging with DC voltage compared to AC voltage. Typically, during withstand voltage tests, the intensities of partial discharges and several other parameters are measured. With DC voltage, the frequency of discharges and the efficiency of erosion are greatly reduced. Meanwhile, regarding the skin effect theory, skin depth of metallic material could be passed by signal at certain frequency level. Regarding lower PD repetition rate and skin effect theory, the author Developed of TEV Sensor which patched on HVDC XLPE Cable. and in accordance with the skin effect theory, a simulation using Ansys AEDT HFSS has done. The results show that in simulation point of view, the signal can leaks over the spherical metal sheath up to around 2 MHz. in experimental work point of view, Capacitive Type Sensor (CTS) can capture signal from pulse generator that injected in XLPE cable. However, the signal captured by CTS was the signal leakage from the end of cable. Additional configuration and future works need to be conduct considering frequency sweeps